Analisa 1 Tesalonika 4:13-14: Peranan Gereja terhadap Perkabungan Jemaat - Christian Rizky Poli; Bara Izzat Wiwah Handaru; Tita Delila Tukunang (LPPM STT Baptis Kalvari, 2023)
The research objectives are to find the principle of mourning for death according to the text of 1 Thessalonians 4: 13-14, analyze the dynamics of the congregation in the context of mourning, and describe the role of the church towards congregations who mourn death. Based on the research objectives, this research will present data in the form of a description of a theoretical concept, hypothesis questions regarding the status of the research subject, namely the verse text. This research uses a qualitative descriptive method to analyze the role of the church towards congregational mourning. This research uses the exegesis approach of Bible study, Bible software, and theological literature review. The research found that the church, as a spiritual and social entity, plays an important role in supporting the congregation in dealing with the grief of death. The church has the capacity to provide the necessary guidance and support in dealing with mourning. . Paul in 1 Thessalonians 4:13-14 provides teaching on the hope of the resurrection of the dead in Christ at the coming of Jesus, as a basis for comfort over the death of a believer. Challenges in mourning can make believers lose hope as believers. It is hoped that this research will guide the Church in understanding and responding to the needs of mourning believers so that it can provide better support according to their context and needs.